Preparation method of high-elastic anti-wrinkle blended fabric

By using silicone quaternary ammonium triazine finishing agent in cotton/spandex blended textiles, the problem of wrinkle resistance and hydrophilicity reduction caused by the finishing agent is solved, and fabric preparation with high elasticity, wrinkle resistance and hydrophilicity is achieved. The firm adhesion of the finishing agent ensures the performance of the fabric after multiple washings.

CN119640590AActive Publication Date: 2025-03-18PUNING PENGYUANSHENG TEXTILE TECH CO LTD

Patent Information

Application Number
CN202411908985.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing cotton/spandex blended fabrics have good wrinkle resistance and flexibility after finishing, but the hydrophobicity of the finishing agent affects the hydrophilic and hygroscopic properties of the fabric, and the finishing agent is prone to fall off after friction or multiple washes, resulting in poor finishing effect.

Method used

The condensation reaction was carried out using aminopropyl-terminated polydimethylsiloxane and bisaldehyde quaternary ammonium monomer, and reduced by sodium borohydride to form an imino group, and then reacted with tripolycyanochloride to obtain an organic silicon quaternary ammonium triazine finishing agent. The finishing agent contains flexible polysiloxane segments and hydrophilic quaternary ammonium groups, which are connected to the fabric surface through chemical bonds to ensure firm adhesion of the finishing agent.

Benefits of technology

It significantly improves the wrinkle resistance and flexibility of the blended textile fabric, maintains the high humidity rejuvenation and hydrophilicity of the fabric, avoids the influence of hydrophobic finishing agents, and the finishing agent is not easy to fall off after multiple washes. The fabric still maintains good wrinkle resistance, hydrophilicity and a flexible and elastic feel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205136690000021
    Figure BDA0005205136690000021
  • Figure BDA0005205136690000031
    Figure BDA0005205136690000031
  • Figure BDA0005205136690000081
    Figure BDA0005205136690000081
Patent Text Reader

Abstract

The invention relates to the technical field of fabrics, and discloses a preparation method of a high-elastic anti-wrinkle blended fabric, which comprises the following steps: adding sodium carbonate, an organosilicon quaternary ammonium salt triazine finishing agent and a cotton / spandex blended fabric into water, soaking, then soaking and rolling twice, washing, and then pre-drying and baking to obtain the high-elastic anti-wrinkle blended fabric. The finishing agent contains cyanuric chloride groups, active chlorine atoms of the cyanuric chloride groups can react with hydroxyl groups of the cotton fabric, so that the finishing agent is connected to the surface of the blended fabric through stable chemical bonds, meanwhile, the finishing agent contains a large number of amido bonds, and the amido bonds and carbamate groups of spandex fabric form hydrogen bond interaction, so that the finishing agent can be used for finishing the cotton fabric. The finishing agent can be firmly attached to the surface of the blended fabric and has good washing resistance, the finishing agent is not prone to falling off after multiple times of washing, and the fabric still has high wrinkle recovery angle, moisture regain and good hand feeling and keeps good wrinkle resistance, hydrophilic performance and soft and elastic hand feeling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabrics, in particular to a method for preparing a high-elastic wrinkle-resistant blended fabric. Background Art

[0002] Cotton fabrics have good hydrophilicity, moisture absorption, warmth retention, heat resistance and other properties, and are widely used in clothing, home textiles, medical and health products, etc. Spandex is a polyurethane fiber with high elasticity, good mechanical properties and excellent wear resistance. Blending cotton fabrics with spandex can produce blended fabrics with better performance. In order to improve the wrinkle resistance, soft and elastic feel and other properties of cotton / spandex blended fabrics, it is usually necessary to finish the fabrics. Common finishing agents include polyamide finishing agents, polyether finishing agents, silicone finishing agents, etc.

[0003] Organic silicon finishing agent is a high-performance finishing agent made of hydrogenated silicone oil, amino silicone oil, polysiloxane, etc., which can improve the wrinkle resistance, softness, comfort and feel of fabrics. However, organic silicon finishing agent has strong hydrophobicity, which will affect the hydrophilic and hygroscopic properties of fabrics. Moreover, after finishing the fabric with finishing agent, after friction or multiple washing or friction, the finishing agent will gradually fall off, resulting in poor finishing effect. Summary of the invention

[0004] (I) Technical problem to be solved: The present invention provides a method for preparing a blended fabric with high elasticity, wrinkle resistance and hydrophilicity.

[0005] (II) Technical solution: A method for preparing a highly elastic and wrinkle-resistant blended fabric:

[0006] Step A, add dichloromethane, aminopropyl-terminated polydimethylsiloxane, and the structural formula The dialdehyde quaternary ammonium salt monomer, wherein a is 2-6 in the structural formula, is stirred at 40-45°C for condensation reaction for 24-36 hours, rotary evaporated, washed with petroleum ether, then added to ethanol, sodium borohydride is added, stirred at 20-30°C for reduction reaction for 3-6 hours, rotary evaporated, dichloromethane and water are added, stirred and allowed to stand for stratification, the aqueous phase is removed, the organic phase is rotary evaporated, and dried to obtain an organosilicon quaternary ammonium salt.

[0007] Step B, add organosilicon quaternary ammonium salt, cyanuric chloride, sodium carbonate and water to 1,4-dioxane, stir and react at 15-25°C for 6-12h, rotary evaporate, add dichloromethane and water, stir and stand to separate, remove the aqueous phase, rotary evaporate the organic phase, and dry to obtain an organosilicon quaternary ammonium salt triazine finishing agent.

[0008] The reaction formula is:

[0009]

[0010] Step C, adding water, 0.3-0.8% sodium carbonate of the mass of water, and 2-5% organosilicon quaternary ammonium salt triazine finishing agent into a container, adding cotton / spandex blended fabric after stirring, heating to 70-80° C., soaking for 1-2 hours, and then performing two dipping and two rolling, with the rolling rate being 80-90%, and pre-baking and baking after washing to obtain a high-elasticity wrinkle-resistant blended fabric.

[0011] Preferably, the mass of the dialdehyde quaternary ammonium salt monomer in step A is 64-71% of the mass of the aminopropyl-terminated polydimethylsiloxane.

[0012] Preferably, the preparation method of the dialdehyde quaternary ammonium salt monomer is:

[0013] Step (1), add dichloromethane, p-formylbenzoic acid, triethylamine (TEA), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDCl), 1-hydroxybenzotriazole (HOBt), and 3-(dimethylamino)-1-propylamine to a reaction vessel, stir and react at 20-30° C. for 12-18 hours, add saturated sodium chloride aqueous solution, stir, stand and separate, remove the aqueous phase, rotary evaporate the organic phase, and separate by silica gel column chromatography to obtain an intermediate.

[0014] Step (2), add isopropanol, intermediate, and dibromoalkane compound to the reaction vessel, heat to 80-85°C, condense and reflux for 36-48h, rotary evaporate, and recrystallize the product in a mixed solution of isopropanol and acetone to obtain a dialdehyde quaternary ammonium salt monomer. The reaction formula is as follows:

[0015]

[0016] Preferably, in step (1), the molar amounts of triethylamine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-hydroxybenzotriazole, and 3-(dimethylamino)-1-propylamine are 120-130%, 140-150%, 140-150%, and 120-130% of the molar amount of p-formylbenzoic acid, respectively.

[0017] Preferably, in step (2), the molar amount of the intermediate is 200-240% of the molar amount of the dibromoalkane compound. The dibromoalkane compound is 1,2-dibromoethane, 1,3-dibromopropane, 1,4-dibromobutane, 1,5-dibromopentane or 1,6-dibromohexane.

[0018] Preferably, in step B, the mass of cyanuric chloride and sodium carbonate is 6-15% and 4-10% of the mass of the quaternary ammonium silicone oil, respectively.

[0019] (III) Technical effect: The present invention conducts condensation reaction of aminopropyl-terminated polydimethylsiloxane and dialdehyde quaternary ammonium salt monomer, and reduces with sodium borohydride. The generated imino group reacts with a chlorine atom of cyanuric chloride to obtain an organosilicon quaternary ammonium salt triazine finishing agent, which is then used to finish cotton / spandex blended fabrics. The finishing agent contains a flexible polysiloxane chain segment, which significantly improves the wrinkle resistance of the blended fabric, exhibits a higher wrinkle recovery angle, and improves the softness, elasticity and other feel of the blended fabric.

[0020] The organosilicon quaternary ammonium salt triazine finishing agent of the invention contains a large amount of hydrophilic quaternary ammonium salt, amide bond, imino group and the like, so as to maintain good moisture regain and hydrophilicity of the blended fabric and avoid the hydrophobic organosilicon finishing agent affecting the hydrophilicity of the fabric.

[0021] The finishing agent of the invention contains cyanuric chloride groups, the active chlorine atoms of which can react with the hydroxyl groups of the cotton fabric, so that the finishing agent is connected to the surface of the blended fabric through a stable chemical bond. Meanwhile, the finishing agent contains a large number of amide bonds, which interact with the urethane groups of the spandex fabric by forming hydrogen bonds, so that the finishing agent is firmly attached to the surface of the blended fabric, has good water washability, is not easy to fall off after multiple water washings, and the fabric still has a high wrinkle recovery angle, moisture regain and good hand feel, and maintains good wrinkle resistance, hydrophilicity and soft elastic hand feel. DETAILED DESCRIPTION

[0022] Aminopropyl-terminated polydimethylsiloxane, molecular weight 1000, Guangdong Fangxin Biotechnology Co., Ltd.

[0023] Cotton / Spandex blend fabric, 95% cotton, 5% spandex.

[0024] Example 1. (1) Into a reaction vessel, 20 mL of dichloromethane, 5 mmol of p-formylbenzoic acid, 6 mmol of triethylamine, 7.5 mmol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 7.5 mmol of 1-hydroxybenzotriazole, and 6 mmol of 3-(dimethylamino)-1-propylamine were added, and the mixture was stirred at 30° C. for 12 h. A saturated aqueous sodium chloride solution was added, stirred, and allowed to stand for stratification. The aqueous phase was removed, and the organic phase was rotary evaporated and separated by silica gel column chromatography to obtain an intermediate.

[0025] (2) Add 60 mL of isopropanol, 10 mmol of the intermediate, and 20 mmol of 1,2-dibromoethane into a reaction container, heat to 80° C., condense and reflux for 48 hours, and rotary evaporate. The product is recrystallized in a mixed solution of isopropanol and acetone to obtain a dialdehyde quaternary ammonium salt monomer.

[0026] Example 2. (1) Add 25 mL of dichloromethane, 5 mmol of p-formylbenzoic acid, 6.5 mmol of triethylamine, 7 mmol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 7 mmol of 1-hydroxybenzotriazole, and 6.5 mmol of 3-(dimethylamino)-1-propylamine to a reaction vessel, stir the reaction at 20°C for 18 h, add saturated aqueous sodium chloride solution, stir, stand to separate, remove the aqueous phase, rotary evaporate the organic phase, and separate by silica gel column chromatography to obtain an intermediate.

[0027] (2) Add 70 mL of isopropanol, 10 mmol of the intermediate, and 24 mmol of 1,6-dibromohexane to a reaction vessel, heat to 85° C., condense and reflux for 36 hours, and rotary evaporate. The product is recrystallized in a mixed solution of isopropanol and acetone to obtain a dialdehyde quaternary ammonium salt monomer.

[0028] Example 3. (1) 300 mL of dichloromethane, 30 g of aminopropyl-terminated polydimethylsiloxane and 19.2 g of dialdehyde quaternary ammonium salt monomer (prepared by Example 1) were added to a reaction vessel, stirred at 40°C for condensation reaction for 36 h, rotary evaporated, washed with petroleum ether, then added to 800 mL of ethanol, 3 g of sodium borohydride was added, stirred at 20°C for reduction reaction for 6 h, rotary evaporated, dichloromethane and water were added, stirred and allowed to stand for stratification, the aqueous phase was removed, the organic phase was rotary evaporated and dried to obtain an organosilicon quaternary ammonium salt.

[0029] (2) Add 40 g of organosilicon quaternary ammonium salt, 2.4 g of cyanuric chloride, 1.6 g of sodium carbonate and 5 mL of water to 400 mL of 1,4-dioxane, stir and react at 25° C. for 12 h, rotary evaporate, add dichloromethane and water, stir and stand to separate, remove the aqueous phase, rotary evaporate the organic phase and dry to obtain an organosilicon quaternary ammonium salt triazine finishing agent.

[0030] (3) Add 1L of water, 3g of sodium carbonate, and 20g of organosilicon quaternary ammonium salt triazine finishing agent into a container, stir, add cotton / spandex blended fabric, heat to 80°C, soak for 1h, and then perform double dipping and double rolling with a rolling rate of 85%. After washing, pre-bake at 85°C for 10min and bake at 160°C for 3min to obtain a highly elastic and wrinkle-resistant blended fabric.

[0031] Example 4. (1) 350 mL of dichloromethane, 30 g of aminopropyl-terminated polydimethylsiloxane, and 19.2 g of dialdehyde quaternary ammonium salt monomer (prepared by Example 2) were added to a reaction vessel, and the mixture was stirred at 45° C. for condensation reaction for 24 h, rotary evaporated, washed with petroleum ether, and then added to 800 mL of ethanol, 3.2 g of sodium borohydride was added, and the mixture was stirred at 30° C. for reduction reaction for 4 h, rotary evaporated, dichloromethane and water were added, stirred and allowed to stand for stratification, the aqueous phase was removed, the organic phase was rotary evaporated, and dried to obtain an organosilicon quaternary ammonium salt.

[0032] (2) Add 40 g of organosilicon quaternary ammonium salt, 6 g of cyanuric chloride, 4 g of sodium carbonate, and 8 mL of water to 600 mL of 1,4-dioxane, stir and react at 15° C. for 6 h, perform rotary evaporation, add dichloromethane and water, stir and allow to stand for stratification, remove the aqueous phase, and perform rotary evaporation of the organic phase and dry to obtain an organosilicon quaternary ammonium salt triazine finishing agent.

[0033] (3) Add 1L of water, 5g of sodium carbonate, and 35g of organosilicon quaternary ammonium salt triazine finishing agent into a container, stir, add cotton / spandex blended fabric, heat to 70°C, soak for 2h, and then perform double dipping and double rolling with a rolling rate of 80%. After washing, pre-bake at 80°C for 10min and bake at 160°C for 3min to obtain a highly elastic and wrinkle-resistant blended fabric.

[0034] Example 5. (1) 400 mL of dichloromethane, 30 g of aminopropyl-terminated polydimethylsiloxane and 21.3 g of dialdehyde quaternary ammonium salt monomer (prepared by Example 1) were added to a reaction vessel, and the mixture was stirred at 40° C. for condensation reaction for 36 h, rotary evaporated, washed with petroleum ether, and then added to 800 mL of ethanol. 2.8 g of sodium borohydride was added, and the mixture was stirred at 30° C. for reduction reaction for 3 h, rotary evaporated, dichloromethane and water were added, stirred and allowed to stand for stratification, the aqueous phase was removed, the organic phase was rotary evaporated, and dried to obtain an organosilicon quaternary ammonium salt.

[0035] (2) Add 40 g of organosilicon quaternary ammonium salt, 4.8 g of cyanuric chloride, 3 g of sodium carbonate, and 8 mL of water to 600 mL of 1,4-dioxane, stir and react at 20° C. for 12 h, rotary evaporate, add dichloromethane and water, stir and stand to separate, remove the aqueous phase, rotary evaporate the organic phase, and dry to obtain an organosilicon quaternary ammonium salt triazine finishing agent.

[0036] (3) Add 1L of water, 8g of sodium carbonate, and 50g of organosilicon quaternary ammonium salt triazine finishing agent into a container, stir, add cotton / spandex blended fabric, heat to 70°C, soak for 2h, and then perform double dipping and double rolling with a rolling rate of 90%. After washing, pre-bake at 85°C for 10min and bake at 160°C for 3min to obtain a highly elastic and wrinkle-resistant blended fabric.

[0037] Comparative Example 1 is an unfinished cotton / spandex blended fabric.

[0038] Comparative Example 2: (1) Add 1L of water, 3g of sodium carbonate, and 20g of aminopropyl-terminated polydimethylsiloxane into a container, stir, add cotton / spandex blended fabric, heat to 80°C, soak for 1h, then perform double dipping and double rolling, with a rolling rate of 85%. After washing, pre-bake at 85°C for 10min and bake at 160°C for 3min to obtain a high-elastic and wrinkle-resistant blended fabric.

[0039] Comparative Example 3: (1) Add 1L of water, 3g of sodium carbonate, and 20g of organosilicon quaternary ammonium salt (prepared by Example 3) into a container, stir, add cotton / spandex blended fabric, heat to 80°C, soak for 1h, then perform double dipping and double rolling, with a rolling rate of 85%. After washing, pre-bake at 85°C for 10min and bake at 160°C for 3min to obtain a high-elastic and wrinkle-resistant blended fabric.

[0040] Comparative Example 4: (1) 300 mL of dichloromethane, 30 g of aminopropyl-terminated polydimethylsiloxane and 19.2 g of terephthalaldehyde were added to a reaction vessel, and the mixture was stirred at 40°C for condensation reaction for 36 h, rotary evaporated, washed with petroleum ether, and then added to 800 mL of ethanol, 3 g of sodium borohydride was added, and the mixture was stirred at 20°C for reduction reaction for 6 h, rotary evaporated, dichloromethane and water were added, stirred and allowed to stand for stratification, the aqueous phase was removed, the organic phase was rotary evaporated, and dried to obtain an organosilicon copolymer.

[0041] (2) Add 40 g of an organosilicon copolymer, 2.4 g of cyanuric chloride, 1.6 g of sodium carbonate, and 5 mL of water to 400 mL of 1,4-dioxane, stir and react at 75° C. for 12 h, and then rotary evaporate. Add dichloromethane and water, stir and allow to stand for stratification, remove the aqueous phase, rotary evaporate the organic phase, and dry to obtain an organosilicon triazine finishing agent.

[0042] (3) Add 1L of water, 3g of sodium carbonate, and 20g of silicone triazine finishing agent into a container, stir, add cotton / spandex blended fabric, heat to 80°C, soak for 1h, and then perform double dipping and double rolling with a rolling rate of 85%. After washing, pre-bake at 85°C for 10min and bake at 160°C for 3min to obtain a highly elastic and wrinkle-resistant blended fabric.

[0043] The wrinkle recovery angle is tested according to GB / T 3819-1997 standard.

[0044] The moisture regain was tested according to GB / T 9995-1997 standard. The test temperature was 20℃ and the relative humidity was 65%.

[0045] A test panel of 10 people working in the textile field used a subjective judgment method to grade the softness, elasticity and feel of blended fabrics by grasping, pinching, touching and grabbing. 1 point means the worst softness, elasticity and feel, 10 points means the best, and the average value is taken.

[0046] The blended fabrics were washed and dried 50 times according to GB / T 8629-2001 standard, and then the wrinkle recovery angle, moisture regain and hand feel were tested.

[0047] Table 1

[0048]

[0049] Table 2

[0050]

[0051] Table 3

[0052]

[0053]

[0054] After testing, Comparative Example 1 is an unfinished cotton / spandex blended fabric, which has good hydrophilicity and moisture regain, but a very low wrinkle recovery angle, poor wrinkle resistance, and poor softness and other hand feel. After the washing and drying process, the wrinkle recovery angle, moisture regain and hand feel have almost no change.

[0055] Example 3-5 uses a silicone quaternary ammonium salt triazine finishing agent to finish cotton / spandex blended fabrics. The finishing agent contains a flexible polysiloxane segment, which significantly improves the wrinkle resistance of the blended fabric, shows a higher wrinkle recovery angle, and improves the softness, elasticity and other feel of the blended fabric. At the same time, the finishing agent contains a large amount of hydrophilic quaternary ammonium salts, amide bonds, imino groups and other groups, so that the blended fabric maintains a good regain and hydrophilicity, and avoids the hydrophobic silicone finishing agent from affecting the hydrophilicity of the fabric. At the same time, after multiple washing and drying procedures, the fabric still has a high wrinkle recovery angle, regain and good feel, which is because the finishing agent contains cyanuric chloride groups. Its active chlorine atoms can react with the hydroxyl groups of cotton fabrics, thereby connecting the finishing agent to the surface of the blended fabric through a stable chemical bond. At the same time, the finishing agent contains a large number of amide bonds. Urethane groups with spandex fabrics The hydrogen bond interaction is formed, so that the finishing agent is firmly attached to the surface of the blended fabric, and the finishing agent is not easy to fall off after repeated washing, thereby maintaining good anti-wrinkle, hydrophilic properties and soft and elastic feel.

[0056] In Comparative Example 2, aminopropyl-terminated polydimethylsiloxane is used as a silicone finishing agent to finish the blended fabric. The wrinkle recovery angle of the fabric becomes larger, and the soft and elastic feel becomes better, but the moisture regain is significantly reduced, the hydrophilicity becomes worse, and after multiple washings, the finishing agent easily falls off from the surface of the fabric, resulting in a smaller wrinkle recovery angle and a worse soft and elastic feel.

[0057] In Comparative Example 3, a blended fabric is finished using a silicone quaternary ammonium salt as a finishing agent. After finishing, the wrinkle recovery angle of the fabric becomes larger, the soft and elastic feel becomes better, the moisture regain and the hydrophilicity are good, but it does not contain cyanuric chloride groups and cannot chemically bond with the hydroxyl groups of the cotton fabric. After multiple washings, the finishing agent easily falls off the fabric surface, the wrinkle recovery angle and moisture regain become smaller, and the soft and elastic feel becomes worse.

[0058] Comparative Example 4 uses terephthalaldehyde as a raw material, and the obtained organosilicon polymer and organosilicon finishing agent do not contain hydrophilic quaternary ammonium salt groups and amide bonds. The moisture regain and hydrophilicity of the finished blended fabric are poor.

Claims

1. A method for preparing a high-elastic wrinkle-resistant blended fabric, characterized in that: The preparation method is as follows: Step A, add dichloromethane, aminopropyl-terminated polydimethylsiloxane, and the structural formula A dialdehyde quaternary ammonium salt monomer, wherein a is 2-6 in the structural formula, is stirred for condensation reaction, rotary evaporated, washed with petroleum ether, then added to ethanol, sodium borohydride is added, stirred for reduction reaction, rotary evaporated, dichloromethane and water are added, stirred and allowed to stand for stratification, the aqueous phase is removed, the organic phase is rotary evaporated, and dried to obtain an organosilicon quaternary ammonium salt; Step B, adding organosilicon quaternary ammonium salt, cyanuric chloride, sodium carbonate and water to 1,4-dioxane, stirring for reaction, rotary evaporation, adding dichloromethane and water, stirring and standing for stratification, removing the aqueous phase, rotary evaporating the organic phase, and drying to obtain an organosilicon quaternary ammonium salt triazine finishing agent; Step C, adding water, sodium carbonate, and organosilicon quaternary ammonium salt triazine finishing agent into a container, stirring, adding cotton / spandex blended fabric, heating to 70-80° C., soaking for 1-2 hours, and then performing double dipping and double rolling, with a rolling rate of 80-90%, and pre-baking and baking after washing to obtain a high-elasticity and wrinkle-resistant blended fabric.

2. The method for preparing a high-elastic wrinkle-resistant blended fabric according to claim 1, characterized in that: In step A, the temperature of the condensation reaction is 40-45° C., and the reaction time is 24-36 hours; the temperature of the reduction reaction is 20-30° C., and the reaction time is 3-6 hours.

3. The method for preparing a high elastic and wrinkle-resistant blended fabric according to claim 1, characterized in that: The mass of the dialdehyde quaternary ammonium salt monomer in step A is 64-71% of the mass of the aminopropyl-terminated polydimethylsiloxane.

4. The method for preparing a high-elastic wrinkle-resistant blended fabric according to claim 3, characterized in that: The preparation method of the dialdehyde quaternary ammonium salt monomer is: Step (1), adding dichloromethane, p-formylbenzoic acid, triethylamine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-hydroxybenzotriazole, and 3-(dimethylamino)-1-propylamine to a reaction vessel, stirring at 20-30° C. for 12-18 hours, adding a saturated sodium chloride aqueous solution, stirring, standing for stratification, removing the aqueous phase, rotary evaporating the organic phase, and separating by silica gel column chromatography to obtain an intermediate; Step (2), adding isopropanol, the intermediate, and the dibromoalkane compound into a reaction vessel, heating to 80-85° C., condensing and refluxing for 36-48 hours, rotary evaporation, and recrystallizing the product in liquid to obtain a dialdehyde quaternary ammonium salt monomer.

5. The method for preparing a high-elastic wrinkle-resistant blended fabric according to claim 4, characterized in that: In the step (1), the molar amounts of triethylamine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-hydroxybenzotriazole, and 3-(dimethylamino)-1-propylamine are 120-130%, 140-150%, 140-150%, and 120-130% of the molar amount of p-formylbenzoic acid, respectively.

6. The method for preparing a high-elastic wrinkle-resistant blended fabric according to claim 4, characterized in that: In the step (2), the molar amount of the intermediate is 200-240% of the molar amount of the dibromoalkane compound; the dibromoalkane compound is 1,2-dibromoethane, 1,3-dibromopropane, 1,4-dibromobutane, 1,5-dibromopentane or 1,6-dibromohexane.

7. The method for preparing a high elastic and wrinkle-resistant blended fabric according to claim 1, characterized in that: In the step B, the mass of cyanuric chloride and sodium carbonate is 6-15% and 4-10% of the mass of the quaternary ammonium silicone oil respectively.

8. The method for preparing a high-elastic wrinkle-resistant blended fabric according to claim 1, characterized in that: The reaction temperature in step B is 15-25° C. and the reaction time is 6-12 h.

9. The method for preparing a high-elastic wrinkle-resistant blended fabric according to claim 1, characterized in that: In the step C, the mass of sodium carbonate and the organosilicon quaternary ammonium salt triazine finishing agent are 0.3-0.8% and 2-5% of the mass of water respectively.

Citation Information

Patent Citations

  • Polysiloxane crease resistant finishing agent composition for natural fiber and preparation method thereof

    CN101671958A

  • Cyanuric chloride derivative as well as preparation method and application in anti-wrinkle finishing agent of cyanuric chloride derivative and finishing method of pure silk fabric

    CN102558078A

  • Anti-crease agent containing isodigeranyl active groups as well as preparation method and application of anti-crease agent

    CN105113252A

  • Preparation method and application of cationic modifier TCTAC

    CN113373691A

  • Avoiding creasing tendency of textiles

    WO2017191094A1

Cited By

  • Antibacterial textile fabric and preparation method thereof

    CN120211120A

  • Cool antistatic comfortable fabric and preparation method thereof

    CN120350555A

  • Cooling antistatic comfortable fabric and preparation method thereof

    CN120350555B

  • Soft moisture-absorbing polyester fabric and preparation method thereof

    CN121138016A